2013
DOI: 10.1093/jrr/rrt017
|View full text |Cite
|
Sign up to set email alerts
|

Geometrical differences in gross target volumes between 3DCT and 4DCT imaging in radiotherapy for non-small-cell lung cancer

Abstract: The aim of this study was to explore the characteristic of 3DCT scanning phases and estimate the comparative amount of respiration motion information included in 3DCT and 4DCT by comparing the volumetric and positional difference between the volumes from 3DCT and 4DCT for the radiotherapy of non-small-cell lung cancer (NSCLC). A total of 28 patients with NSCLC sequentially underwent 3DCT and 4DCT simulation scans of the thorax during free breathing. The 4DCT images with respiratory signal data were reconstruct… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
22
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 21 publications
(25 citation statements)
references
References 26 publications
(32 reference statements)
3
22
0
Order By: Relevance
“…One approach to define tumor motion is to contour gross target volumes (GTVs) on ten phases of 4DCT and obtain internal gross target volume (IGTV) by combining them; theoretically, this would give information about the entire tumor motion 7,8…”
Section: Introductionmentioning
confidence: 99%
“…One approach to define tumor motion is to contour gross target volumes (GTVs) on ten phases of 4DCT and obtain internal gross target volume (IGTV) by combining them; theoretically, this would give information about the entire tumor motion 7,8…”
Section: Introductionmentioning
confidence: 99%
“… 6 Temporal images acquired during conventional axial three-dimensional computed tomography (3DCT) may include limited respiratory motion details for determining the target margin, but it has been difficult to evaluate how much motion information the 3DCT provides. 7 In contrast, the four-dimensional computed tomography (4DCT) is a reliable and effective tool for assessing tumor motion. 8 4DCT enables the correlation of CT data acquisition with respiratory cycles, facilitating the acquisition of a series of 3DCT data sets over a patient’s breathing cycle to provide visualization of tumor motion on an individual patient basis.…”
Section: Introductionmentioning
confidence: 99%
“…Several studies showed that lower lobe tumor motions occurred mostly in the SI direction and had larger amplitude movement than upper lobe tumors. 18,19) In addition, large tumor motion may be more closely associated with the difference between the 3D and 4D dose calculations than small motion. Therefore, the phantom simulated a tumor located in the lower lobe.…”
Section: Discussionmentioning
confidence: 99%